2014
DOI: 10.4110/in.2014.14.5.255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endurance Training on the Serum Levels of Tumour Necrosis Factor-α and Interferon-γ in Sedentary Men

Abstract: Physical activity could be considered one of the factors that affect the immune system status and function. To find the relation between exercise and cytokines, we examined the possible effects of an 8-week endurance training program on the serum levels of cytokines, including tumour necrosis factor-alpha (TNF-α) and interferon-gamma (IFN-γ) in sedentary men. A total of 30 healthy young male volunteers were randomly divided into an endurance training group and a control group. The training group followed a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 21 publications
1
10
1
1
Order By: Relevance
“…The reaction of cytokines to training was multiplex and associated with the intensity of the training, exercise situations, site of cytokine evaluation (e.g. tissue, plasma or urine), and sensibility of measurement process (22). This study wasn't consistent with the current study and this difference can be due to differences in subjects, measurement methods, and differences in exercise protocols.…”
Section: Discussioncontrasting
confidence: 73%
“…The reaction of cytokines to training was multiplex and associated with the intensity of the training, exercise situations, site of cytokine evaluation (e.g. tissue, plasma or urine), and sensibility of measurement process (22). This study wasn't consistent with the current study and this difference can be due to differences in subjects, measurement methods, and differences in exercise protocols.…”
Section: Discussioncontrasting
confidence: 73%
“…The heart rates of all the participants were recorded for the maximal heart rate calculation using Karvonen method ( 14 ) as follows: HR target=% Intensity (HR max−HR rest)+HR rest …”
Section: Methodsmentioning
confidence: 99%
“…The fact that TNF-␣ upregulation correlated with the upregulation of ANF, collagen type 1␣ 2 , and the increase in LVESV suggests that inflammation is an important signaling mechanism that contributes to LV remodeling processes. Anti-inflammatory effects of exercise per se have been already widely discussed (28,60). In the context of myocardial injury, it has been previously reported that endurance training reduces TNF-␣ levels in plasma of patients with heart failure (1) and in the soleus muscle of infarcted rats (3).…”
Section: H355 Exercise Limits Post-mi Scar Thinningmentioning
confidence: 99%